EKSPLORASI ETNOMATEMATIKA TERHADAP TRANSFORMASI GEOMETRI PADA BATIK MALEFO - Bustan, Ariestha Widyastuty; Salmin, Munazat; Talib, Taufan (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2021)
Abstract mathematical concepts require using objects around the student's environment to make mathematical concepts more concrete. One of the objects around that can be used is a cultural object. In particular, the approach that links mathematics with culture is the ethnomathematical approach. This study explores the ethnomathematics of the geometric transformation material on malefo batik, a typical batik of Ternate City. This type of research is qualitative research with an ethnographic approach. Data was collected using literature study, observation, interview, and documentation methods. The subject of this research is the owner of the Malefo batik gallery. The data obtained in this study came from direct observation, interviews with research subjects, and document results. The results of the study found that the motifs used in malefo batik can be a concrete example of the types of geometric transformations, namely the translational type of geometric transformation on the clove and machete flower arrangement batik motifs, the type of reflection on the clove flower motif, nutmeg, salawaku, parang and coconut flowers, the type of dilatation in the dodia batik motif, as well as the rotation type in the clove and clove flower motifs. The examples represented in Malefo batik can then be recommended as an alternative learning media to understand the material of geometric transformation better